Cascaded interpolation‐filter‐delay‐decimation algorithm without additional delay. Issue 5 (1st July 2017) - Guo, Wei; Yan, Yili; Jia, Min; Wu, Xiaoming; Tang, Chi
Abstract : Accurate time delay is indispensable for many sorts of signal processing applications particular in the field of communication and detection. Traditionally, due to easy operation, interpolation‐filter‐delay‐decimation (IFDD) algorithm was regarded as an intuitive and straightforward way to delay specific signals. However, the computational complexity of this approach will increase sharply with the increase of interpolation factor. In addition, the IFDD algorithm will also induce a fixed additional delay in the delayed signal, limiting its widespread application. To solve these issues, this study presented a cascaded IFDD algorithm without additional delay (C‐IFDD‐WAD) by decomposing the large interpolation factor into several small interpolation factors. The authors obtained the expression of C‐IFDD‐WAD algorithm and analysed the spectrum characteristics of C‐IFDD‐WAD algorithm in this study. Their theoretical analysis combined with the simulation results show that the computation cost of C‐IFDD‐WAD significantly decreased in the form of cascade based on their present new method. Moreover, the additional delay of traditional IFDD algorithm was also eliminated using the present method.